Exploring learning, identity, and power through life history and narrative research - Bathmaker, Ann-Marie; Harnett, Penelope (Routledge, 2010)
Brings together a collection of writing by different authors who use a narrative/life history approach to explore the experiences of a wide range of people, reflecting on learning and education at significant moments in their lives.